2017
DOI: 10.18632/oncotarget.19978
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic steatohepatitis-related liver tumorigenesis is suppressed in mice lacking hepatic retinoid storage

Abstract: Non-alcoholic fatty liver disease has become one of the most common causes of chronic liver disease that can develop into a more serious form, non-alcoholic steatohepatitis, leading to liver cirrhosis and hepatocellular carcinoma. Although hepatic retinoid stores are progressively lost during the development of liver disease, how this affects steatohepatitis and its related hepatocarcinogenesis is unknown. In order to investigate these, we used subcutaneous injection of streptozotocin (0.2 mg/body) and high-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The long-term chronic inflammatory in obesity plus higher IL-6 and TNF might be the risk factor for HCC [118]. The prospective studies (25,337 patients with HCC) demonstrated that both of excess body weight and obesity in males or females are related to an increased risk factor for HCC occurrence [119]. The prospective studies with longer follow-up periods should screen the malignant transformation of hepatocytes with specific biomarkers among NASH or NAFLD populations [3,120].…”
Section: Nafld In Hepatocarcinogenesismentioning
confidence: 99%
“…The long-term chronic inflammatory in obesity plus higher IL-6 and TNF might be the risk factor for HCC [118]. The prospective studies (25,337 patients with HCC) demonstrated that both of excess body weight and obesity in males or females are related to an increased risk factor for HCC occurrence [119]. The prospective studies with longer follow-up periods should screen the malignant transformation of hepatocytes with specific biomarkers among NASH or NAFLD populations [3,120].…”
Section: Nafld In Hepatocarcinogenesismentioning
confidence: 99%